On Shelf - "Srivastava, I.C. (ed.);Joshi, B.D. (ed.)" (Jaipur, 2012)
This book will serve as a reference and research material for those who seek to explore, analyse and learn from the nuances of administrative action.
Keywords: Bureaucracy-India